Separation of Digital Audio Signals using Least-Mean-Square (LMS) Adaptive Algorithm - Kayode F. Akingbade; Isiaka A. Alimi (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Adaptive filtering is one of the fundamental technologies in digital signal processing (DSP) in today’s communication systems and it has been employed in a wide range of applications such as adaptive noise cancellation, adaptive equalization, and echo cancellation.Signal separation remains a task that has called for attention in digital signal processing and different techniques have been employed in order to achieve efficient and accurateresult. Implementation of adaptive filtering can separate wanted and interference signals so as to improve performance of communication systems. In the light of this, this paper usesa least-mean-square (LMS) adaptive algorithm for separation of audio signals.The simulated results show that the designed LMS based adaptive filtering techniqueconverge faster than conventional LMS adaptive filter.DOI:http://dx.doi.org/10.11591/ijece.v4i4.6219